Hypertension update and cardiovascular risk reduction in physically active individuals and athletes - Oliveira, L. P. J.; Lawless, C. E. (The Physician and Sportsmedicine, 2010)
Hypertension is a prevalent disease worldwide. Its inadequate treatment leads to major cardiovascular complications, such as myocardial infarction, stroke, and heart failure. These conditions decrease life expectancy and are a substantial cost burden to health care systems. Physically active individuals and professional athletes are not risk free for developing this condition. Although the percentage of persons affected is substantially lower than the general population, these individuals still need to be thoroughly evaluated and blood pressure targets monitored to allow safe competitive sports participation. Regarding treatment, lifestyle modification measures should be routinely emphasized to athletes and active individuals with the same importance as for the general population. Medication treatment can be complicated because of restrictions by athletic organizations and possible limitations on maximal exercise performance. In addition, the choice of an antihypertensive drug should be made with consideration for salt and water losses that routinely occur in athletes, as well as preservation of exercise performance and endothelial function. First-line therapies for athletes and physically active individuals may be different from the general population. Some authorities believe that blocking the renin-angiotensin system with angiotensin-converting enzyme (ACE) inhibitors or angiotensin receptor blockers (ARBs) is more beneficial compared with diuretics because of ACE inhibitors and ARBs being able to avoid salt and water losses. Dihydropyridine calcium channel blockers (CCBs) are another reasonable choice. Despite effects on heart rate, nondihydropyridine CCBs do not appear to impair exercise performance.ß-Blockers are not used as a first-line therapy in athletes because of effects on exercise and prohibition by the National Collegiate Athletic Association and World Anti-Doping Agency in certain sports. In this article, we address the evidence on hypertension and its related treatments in active individuals to provide recommendations that allow the best competitive sports results and reduce cardiovascular risk.